Development of Android-Based Learning Media in The Subjects of Planning and Installation Video Audio System - Joni Andrian; Hasan Maksum (EDUTEC : Journal of Education And Technology, 2020)
This research aims to produce products in the form of android-based learning media that are valid, practical and effective in the subjects of Planning and Installation of Audio Video Systems. Development of android-based learning media using R&D research method with 4D development procedure (define, design, development and disseminate). The subjects in this study were students of class XII Audio Video Engineering SMK Negeri 1 Batipuh. The results showed the feasibility of android-based learning media with media expert test results obtained an average of 89% with the category "valid". Material expert test results obtained an average of 90% with the category "valid". The results of the teacher practicality questionnaire test were obtained an average of 93.85 with a "very practical" category. The results of the study of practicality questionnaires of learners were obtained an average of 88.67 with a category of "very practical". The N-Gain Score test result for the experimental class was 79.6% with the "High" category while the average N-Gain Score for the control class was 38.9% with the "Low" category. So, android-based learning media developed effectively used as a learning media in the subjects of Planning and Installation System Audio Video.